Comprehensive plasma and tissue profiling reveals systemic metabolic alterations in cardiac hypertrophy and failure. Issue 8 (9th November 2018) - Müller, Oliver J; Heckmann, Markus B; Ding, Lin; Rapti, Kleopatra; Rangrez, Ashraf Y; Gerken, Thomas; Christiansen, Nicole; Rennefahrt, Ulrike E E; Witt, Henning; González Maldonado, Sandra; Ternes, Philipp; Schwab, Dominic M; et al.
Abstract : Aims: Heart failure is characterized by structural and metabolic cardiac remodelling. The aim of the present study is to expand our understanding of the complex metabolic alterations in the transition from pathological hypertrophy to heart failure and exploit the results from a translational perspective. Methods and results: Mice were subjected to transverse aortic constriction (TAC) or sham surgery and sacrificed 2 weeks, 4 weeks, or 6 weeks after the procedure. Samples from plasma, liver, skeletal muscle, and heart were collected and analysed using metabolomics. Cardiac samples were also analysed by transcriptional profiling. Progressive alterations of key cardiac metabolic pathways and gene expression patterns indicated impaired mitochondrial function and a metabolic switch during transition to heart failure. Similar to the heart, liver, and skeletal muscle revealed significant metabolic alterations such as depletion of essential fatty acids and glycerolipids in late stages of heart failure. Circulating metabolites, particularly fatty acids, reflected cardiac metabolic defects, and deteriorating heart function. For example, inverse correlation was found between plasma and the heart levels of triacylglycerol (C18:1, C18:2, C18:3), and sphingomyelin (d18:1, C23:0) already at an early stage of heart failure. Interestingly, combining metabolic and transcriptional data from cardiac tissue revealed that decreased carnitine shuttling and transportation preceded mitochondrial dysfunction. We, thus, studied the therapeutic potential of OCTN2 (Organic Cation/Carnitine Transporter 2), an important factor for carnitine transportation. Cardiac overexpression of OCTN2 using an adeno-associated viral vector significantly improved ejection fraction and reduced interstitial fibrosis in mice subjected to TAC. Conclusion: Comprehensive plasma and tissue profiling reveals systemic metabolic alterations in heart failure, which can be used for identification of novel biomarkers and potential therapeutic targets. Graphical Abstract: